2019
DOI: 10.3390/ma12162590
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Optimal Machining Conditions and Energy Efficiency in Plasma Assisted Machining of Ti-6Al-4V

Abstract: This research objective was to determine the significant parameters for effective plasma assisted machining (PAM) of Ti-6Al-4V and to derive optimal processing conditions. PAM parameters such as feed rate, spindle speed, and depth of cut have significant effects on its machining characteristic. In this study, the design of experiments (DOE) was used to select optimal machining conditions for PAM. The signal-to-noise (S/N) ratio was analyzed using the Taguchi method and the contributions of the factors were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The workpiece and torch distance are maintained at a fixed distance. Additionally, transfer type is more challenging to utilize because it only functions on conductive materials [7,8,9]. The thermal power can be estimated as follows if it is assumed that the heat spread is uniform:…”
Section: Induction Heatingmentioning
confidence: 99%
See 2 more Smart Citations
“…The workpiece and torch distance are maintained at a fixed distance. Additionally, transfer type is more challenging to utilize because it only functions on conductive materials [7,8,9]. The thermal power can be estimated as follows if it is assumed that the heat spread is uniform:…”
Section: Induction Heatingmentioning
confidence: 99%
“…For Ti-6Al-4V the force on tool was reduced by 60.2% and Ra by 0.376 µm to 0.111 µm. When compared to conventional heating, plasma assisted machining (PAM) resulted in a surface roughness improvement of 70.47%, and its specific cutting energy was 32.9 N/mm 2 [8].…”
Section: Plasma Assisted Machining Processmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the issues associated with conventional machining of hard-to-cut materials, advanced and hybrid machining processes have been researched. These include Cryogenic cooling [3], Minimum quantity lubrication (MQL) [4], Vibration-assisted machining (VAM) [5], modi cation of cutting tool surface with different micro-textures using femtosecond laser [6], and various Thermal-assisted machining (TAM) processes like Plasma-assisted machining (PAM) [7], Induction-assisted machining (IAM) [8], and Laser-assisted machining (LAM) [9][10][11][12][13][14][15][16][17][18][19][20]. In recent years, LAM has become the preferred alternative due to the favorable properties of laser beams, such as good focusing ability, localized heating, and ease of automation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of Kim et al [ 17 ], induction assisted milling of Inconel 718 has been reported and optimized process parameters are proposed. For the same analogy, plasma has been used as an assisting source of energy to machine Ti 6Al 4V, and the process is termed as plasma-assisted machining [ 18 ]. In this way, by the use of additional source of energy to soften the localized area ahead of the cutting tool, the cutting forces can be reduced and tool life can be enhanced by minimizing the frequency of tool failure.…”
Section: Introductionmentioning
confidence: 99%